The Significance of Demographic Changes Occurring in the Canadian East Arctic - Freeman, Milton M. R. (Anthropologica, 2022)
This essay investigates the relationship existing between fertility and development in the Canadian North. The high rate of population increase, rather than population size itself, is seen as a major impediment to development in regions having the demographic characteristics similar to those extant in the Arctic. Economic, social and political consequences of high fertility in such areas are discussed, and the principle reiterated that no rational social and economic development programs can be formulated which ignore rationalization of fertility through extension of medical services. In view of prevailing attitudes in Canadian society toward population control programs, the prognosis for successful development of human resources in high fertility regions of Canada appears to be poor.